2010
DOI: 10.1017/s0007114510001790
|View full text |Cite
|
Sign up to set email alerts
|

Developmental origins of cardiovascular risk in Jamaican children: The Vulnerable Windows Cohort Study

Abstract: Both intra-uterine and early childhood development contribute to the risk of developing CVD in adult life. We therefore evaluated the maternal, placental, fetal, birth, infant and childhood determinants of cardiovascular risk in a cohort of Afro-Jamaican children. The Vulnerable Windows Cohort is a longitudinal survey of 569 mothers and their offspring recruited from the first trimester. The offspring's anthropometry was measured at birth, at 6 weeks, every 3 months to 1 year and then every 6 months. At mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…Some found a greater influence of the mother's than the father's BMI on offspring BMI (7,(11)(12)(13) or fat mass (14) , while others have reported that both predict offspring BMI (6,(15)(16)(17)(18)(19)(20) or fat mass equally (19) . Only a few studies have reported associations between maternal adiposity and childhood CVD risk factors such as blood pressure (8,21,22) , lipid profile (23) and insulin resistance (24) . Studies examining associations between paternal adiposity and CVD risk factors in children are scarce.…”
mentioning
confidence: 99%
“…Some found a greater influence of the mother's than the father's BMI on offspring BMI (7,(11)(12)(13) or fat mass (14) , while others have reported that both predict offspring BMI (6,(15)(16)(17)(18)(19)(20) or fat mass equally (19) . Only a few studies have reported associations between maternal adiposity and childhood CVD risk factors such as blood pressure (8,21,22) , lipid profile (23) and insulin resistance (24) . Studies examining associations between paternal adiposity and CVD risk factors in children are scarce.…”
mentioning
confidence: 99%
“…2. Mean SBP was related to rapid postnatal catch-up growth in five studies, 21,30,36,39,55 significantly so in three of them. 30,36,55 3.…”
Section: Findings Related To the Rapid Catch-up Growth Hypothesismentioning
confidence: 91%
“…30,36,55 3. Mean DBP was related to BW and rapid catch-up growth in four studies, 30,36,39,55 three of which 30,36,39 had statistically significant findings. In one other study, 21 it was equal in cases and controls.…”
Section: Findings Related To the Rapid Catch-up Growth Hypothesismentioning
confidence: 93%
See 2 more Smart Citations